Umbrella parade - Feczko, Kathy; Borgo, Deborah Colvin (Mahwah, N.J. : Troll Associates, 1985)
Each animal uses a different colored umbrella while walking in the rain.
Keywords: Color -- Fiction; Animals -- Fiction; Umbrellas -- Juvenile fiction